2005
DOI: 10.1017/s0021932005001045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Demand Factors, Quality of Care and Access to Facilities on Contraceptive Use in Tanzania

Abstract: The low contraceptive prevalence rate and the existence of unmet demand for family planning services present a challenge for parties involved in family planning research in Tanzania. The observed situation has been explained by the demand-side variables such as socioeconomic characteristics and cultural values that maintain the demand for large families. A small, but growing body of research is examining the effect of supply-side factors such as quality of care of family planning services on the demand for con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…Only one previous multi-level study has been conducted in sub-Saharan Africa. This prior study, conducted in Tanzania, also found an association between the information provided to clients and current contraceptive use [15]. However, this earlier study measured information by the availability of educational and promotional material, rather than discussion of side effects, method selection, or proper method use, making comparisons between the two studies problematic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one previous multi-level study has been conducted in sub-Saharan Africa. This prior study, conducted in Tanzania, also found an association between the information provided to clients and current contraceptive use [15]. However, this earlier study measured information by the availability of educational and promotional material, rather than discussion of side effects, method selection, or proper method use, making comparisons between the two studies problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies conducted in Peru, Egypt, and Morocco in the late 1980s and early 1990s found little to no effect of quality on method use or continuation [1214]. Conversely, studies conducted between 1991 and 2003 in Tanzania, Egypt, the Philippines, and Nepal found moderate to strong associations between service quality and use [1518]. Possible explanations for conflicting results among existing multi-level studies include variations in the way that quality is defined and measured.…”
mentioning
confidence: 99%
“…However, there has been an increase in the number of babies born outside registered marriages and an increase in the number of people living in de facto relationships. Previous research suggests that childlessness is influenced by marital status [41-43] with the unmarried more likely to remain childless. Marital status may influence a woman's health and wellbeing however due to the small sample size it was not possible to test for associations between marital status and physical and mental health and wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…ensuring continued engagement with services) [1219]. Providing decision makers in developing countries, including in Africa, with the best available evidence on the factors that determine the quality of care in family planning services, from the perspective of clients and health care providers, is important to inform the design and implementation of the most effective, efficient and acceptable measures.…”
Section: Introductionmentioning
confidence: 99%